Da sociedade disciplinar à sociedade de controle : protagonismos e caminhos da educação diante das mudanças de regimes de poder - Carvalho, Lucas de Oliveira (2020)
This work sought to bring a theoretical exercise of the concept of power through the disciplinary society of Michel Foucault and the control society of Gilles Deleuze. We aim to reflect how the school, as an institution of modernity, is being impacted by changes in the logic of functioning power relations with the updating of a disciplinary society to a society of control. And how it has penetrated and achieved its autonomy and sovereignty as an institution of confinement. Since power in the controlling society acts in an "open" mode. That is, outside the logic of confinement typical of the disciplinary society to which the school was instituted. We seek through the analysis of the relationship and institutional tensions between school and family, the production and regulation of new forms of violence and the performance of two political movements, the school without party and the recent occupations of the secondary, bring clues who have characterized this process of updating and transformation that has permeated the school.